The Nuclear RNA-binding Protein Sam68 Translocates to the Cytoplasm and Associates with the Polysomes in Mouse Spermatocytes - Paronetto, Maria Paola (The American Society for Cell Biology, 2006)
Translational control plays a crucial role during gametogenesis in organisms as different as worms and mammals. Mouse knockout models have highlighted the essential function of many RNA-binding proteins during spermatogenesis. Herein we have investigated the expression and function during mammalian male meiosis of Sam68, an RNA-binding protein implicated in several aspects of RNA metabolism. Sam68 expression and localization within the cells is stage specific: it is expressed in the nucleus of spermatogonia, it disappears at the onset of meiosis (leptotene/zygotene stages), and it accumulates again in the nucleus of pachytene spermatocytes and round spermatids. During the meiotic divisions, Sam68 translocates to the cytoplasm where it is found associated with the polysomes. Translocation correlates with serine/threonine phosphorylation and it is blocked by inhibitors of the mitogen activated protein kinases ERK1/2 and of the maturation promoting factor cyclinB-cdc2 complex. Both kinases associate with Sam68 in pachytene spermatocytes and phosphorylate the regulatory regions upstream and downstream of the Sam68 RNA-binding motif. Molecular cloning of the mRNAs associated with Sam68 in mouse spermatocytes reveals a subset of genes that might be posttranscriptionally regulated by this RNA-binding protein during spermatogenesis. We also demonstrate that Sam68 shuttles between the nucleus and the cytoplasm in secondary spermatocytes, suggesting that it may promote translation of specific RNA targets during the meiotic divisions.